Evaluasi Batas Nilai Efektif Kadar Sn Menggunakan Analisis Mikroskop dan UC Balance - Irham Firmansyah; Solihin; Rully Nurhasan (Jurnal Riset Teknik Pertambangan, 2022)
Abstract. PT X has been processing residual tin ore (SHP), land mining and marine mining with a grade of <70%. In order to increase the levels of tin and its associated mineral products to high grade >70% as a requirement for the smelting stage. Tin ore will be analyzed to determine the % content of the sample. Assay analysis can be carried out using a microscope analysis process, unit coefficient balance and chemistry. Microscopy analysis method obtained an average percentage of Sn content of 58.79%, UC Balance analysis of 66.92% and chemical analysis of 58.91%. The level of accuracy produced by the UC Balance analysis tool is the biggest influence on the % of Sn content produced, because it only weighs the specific gravity of cassiterite. The other factors that affect the high error rate generated by the UC Balance analysis are the quality, size, and density of minerals. Meanwhile, the microscope analysis experienced a decrease in the level of accuracy because it was influenced by the quality of the sample and the accuracy of the analyst in distinguishing the types of minerals in each sample. Associated minerals such as ilmenite, zircon, monazite, pyrite and quartz affect the results of the Sn content that will be obtained. The recommended limit for the effective value of microscopy analysis is > 60% and UC Balance analysis is > 70% based on the results of % overall levels. Abstrak. PT X telah melakukan pengolahan bijih timah sisa hasil pengolahan (SHP), penambangan darat dan penambangan laut dengan kadar <70%. Guna meningkatkan kadar timah dan produk mineral ikutannya menjadi high grade >70% sebagai syarat menuju tahap peleburan. Biji timah akan dianalisis untuk mengetahui % kadar sampel. Analisis kadar dapat dilakukan menggunakan proses analisis mikroskop, unit coeficient balance dan kimia. Metode analisis mikroskop mendapatkan hasil ratarata persen kadar Sn sebesar 58,79 %, analisis UC Balance sebesar 66,92 % dan analisis kimia sebesar 58,91 %. Tingkat ketelitian yang dihasilkan oleh alat analisis UC Balance menjadi pengaruh terbesar terhadap % kadar Sn yang dihasilkan, karena hanya menimbang berat jenis kasiterit saja. Adapun faktor lain yang mempengaruhi tingginya tingkat kesalahan yang dihasilkan analisis UC Balance yaitu kualitas, ukuran, berat jenis mineral. Sedangkan pada analisis mikroskop mengalami penurunan tingkat ketelitian karena dipengaruhi oleh kualitas sampel dan ketelitian juru analis dalam membedakan jenis-jenis mineral pada setiap sampel. Mineral ikutan seperti ilmenite, zircon, monazite, pyrit dan kuarsa mempengaruhi hasil nilai kadar Sn yang akan didapatkan. Rekomendasi batas nilai efektif analisis mikroskop > 60 % dan analisis UC Balance > 70 % berdasarkan dari hasil % kadar keseluruhan.